Impact of adhesive ingredients on adhesion between rubber and brass‐plated steel wire in tire - Chowdhury, Soumya Ghosh; Chanda, Jagannath; Ghosh, Sreedip; Banerjee, Koushik; Banerjee, Shib Shankar; Das, Amit; Ghosh, Prasenjit; Bhattacharyya, Sanjay Kr; Mukhopadhyay, Rabindra (Polymer engineering and science, 2020)
Proficiency on underlying mechanism of rubber‐metal adhesion has been increased significantly in the last few decades. Researchers have investigated the effect of various ingredients, such as hexamethoxymethyl melamine, resorcinol, cobalt stearate, and silica, on rubber‐metal interface. The role of each ingredient on rubber‐metal interfacial adhesion is still a subject of scrutiny. In this article, a typical belt skim compound of truck radial tire is selected and the effect of each adhesive ingredient on adhesion strength is explored. Out of these ingredients, the effect of cobalt stearate is found noteworthy. It has improved adhesion strength by 12% (without aging) and by 11% (humid‐aged), respectively, over control compound. For detailed understanding of the effect of cobalt stearate on adhesion, scanning electron microscopy and energy dispersive spectroscopy are utilized to ascertain the rubber coverage and distribution of elements. X‐ray photoelectron spectroscopy results helped us to understand the impact of CuXS layer depth on rubber‐metal adhesion. The depth profile of the CuXS layer was found to be one of the dominant factors of rubber‐metal adhesion retention. Thus, this study has made an attempt to find the impact of different adhesive ingredients on the formation of CuXS layer depth at rubber‐metal interface and establish a correlation with adhesion strength simultaneously.